Evaluation of Antispasmodic Potential of Polyherbal Formulation - Shamkuwar, Prashant (Asian Journal of Biological and Life Sciences, 2020)
The aim of the present study was to investigate the antispasmodic efficacy of polyherbal formulation prepared using extract of Apium graveolens, Helicteres isora and Mentha piperita with excipients. Antispasmodic effectiveness of polyherbal formulation was assessed by inhibition of the spasams induced by different spasmogens. The spasmolytic activity of polyherbal formulation was studied in isolated guinea pig ileum model using acetyl choline, nicotine and histamine as agonist. Effect on gastrointestinal motility was assessed by charcoal meal test in mice. The results of the study demonstrated that polyherbal formulation showed significant reduction of spasm induced by acetyl choline, nicotine and histamine in isolated guinea pig ileum. Polyherbal formulation has also inhibited the intestinal motility in mice. Polyherbal formulation was found to be the potent spasmolytic medication. Mechanism of the antispasmodic activity of polyherbal formulation is non-specific and may be mediated by inhibiting the muscarinic, nicotinic and histamine receptors.
Keywords: Antispasmodic; Acetyl choline; Histamine and Polyherbal formulation; Nicotine